Research on Mechanical Aging Behavior of Grease in Rolling Bearing - Jialong Yang; Yuhao Zhang; Zongzheng Wang; Wei Pu (Chinese Journal of Mechanical Engineering)
Abstract Grease is extensively used in rolling bearings due to its inherent sealing properties. However, mechanical degradation typically occurs, resulting in a significantly shorter lifespan for the grease compared to the bearing. Investigating aging mechanisms is essential. This study utilized rolling bearings to obtain mechanically aged greases. The aged samples were then subjected to do rheological test, FTIR test and friction test to examine the effects of aging time, radial load, and rotational speed. An innovative disk-ball-disk device was developed to study the friction characteristics of aged grease in rolling bearings. Additionally, a grease lubrication and friction model were proposed to further evaluate the lubrication performance of aged grease, using measured rheological parameters and the kinematic velocities of the disk-ball-disk device as inputs. The calculated friction coefficients matched well with disk-ball-disk experimental results. FTIR analysis revealed that the non-soap thickener's structure remained stable, but additives depleted at high speeds. The structure of lithium soap thickener decomposed severely, leading to oil bleeding and a shortened replenishment duration. Over aging time, both greases had lower friction and viscosity due to gradual thickener breakdown, releasing bled oil and extending replenishment. Radial load minimally affected the properties of aged grease. This study may provide valuable insights into the aging mechanisms of grease and the enhancement of rolling bearing lubrication.